Effects of water/ionic liquid ratios on the physicochemical properties of high amylose maize starch-lauric acid complex. (February 2023) - Liu, Pengfei; Dong, Yuhan; Gao, Wei; Wu, Zhengzong; Yu, Bin; Yuan, Chao; Cui, Bo
Abstract: This study examined high amylose maize starch (HAMS) treated with different ratios of a water/ionic liquid (IL) mixture and mixed with lauric acid (LA) and heated to form an amylose-lipid complex. IL can destroy the granule structure of starch, which releases more linear starch chains during the subsequent heating process and promotes the complexation reaction between HAMS and LA. Following the IL treatment of starch, HAMS's diffraction intensities, thermal stability and short-range order structure all decreased. The diffraction intensity of HAMS-LA complexes showed the following order: water:IL-4:1 > water:IL-8:1 > water:IL-2:1 > water:IL-11:1 > water:IL-0.5:1 > untreated sample. The creation of the V-type complex, according to a thermogravimetric study, improved the thermal stability of IL-treated HAMS. Results from Fourier transform infrared and Raman spectroscopy indicate that when IL-treated HAMS interacted with LA, the degree of short-range order structure of complexes increased. Graphical abstract: Image 1 Highlights: The formation of HAMS-lipid complex was affected by the ratio of water/AMIMCL. The moderate concentration of AMIMCL would conductive to inclusion complex production. AMIMCL pretreatment could improve the complexation ability of HAMS.